Physics from planet Earth - an introduction to mechanics - Amato, Joseph C.; Galvez, Enrique Jose, 1956- (CRC Press, Taylor & Francis Group, 2015)
Physics from Planet Earth - An Introduction to Mechanics presents a clear and concise exposition of classical mechanics with an emphasis on the conservation laws. The book guides you on a journey beyond standard approaches that use blocks, projectiles, and inclined planes to grander themes involving interplanetary travel, exoplanetse, asteroid collisions, and dark matter.